2016
DOI: 10.1007/s11626-016-0105-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial phosphatase PGAM5 regulates Keap1-mediated Bcl-xL degradation and controls cardiomyocyte apoptosis driven by myocardial ischemia/reperfusion injury

Abstract: Phosphoglycerate mutase 5 (PGAM5) is a mitochondrial membrane protein that plays crucial roles in necroptosis and apoptosis. Though PGAM5 is known to be required for inducing intrinsic apoptosis through interacting with BCL2 associated X protein (Bax) and dynamin-related protein 1 (Drp1), the expression and role of PGAM5 in cardiomyocyte apoptosis driven by myocardial ischemia/reperfusion injury(MIRI) has not been studied. The present study shows that PGAM5 expression decreased after MIRI in vivo, positively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…The role of PGAM5 in HCC chemoresistance has not been established; previous reports have suggested that PGAM5 may be involved in apoptosis by interacting with Bcl-xL 31 . Interestingly, silencing PGAM5 reduced expression of the anti-apoptotic protein Bcl-xL in 7402 and HepG2 cells by western blotting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The role of PGAM5 in HCC chemoresistance has not been established; previous reports have suggested that PGAM5 may be involved in apoptosis by interacting with Bcl-xL 31 . Interestingly, silencing PGAM5 reduced expression of the anti-apoptotic protein Bcl-xL in 7402 and HepG2 cells by western blotting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PGAM5 is also a binding protein of the antiapoptotic protein, BCL-XL [31]. A decrease in PGAM5 may lead to KEAP1-mediated BCL-XL degradation, which thereby promotes apoptosis [32]. In particular, considering the reduction of NFE2L2 or PGAM5 in aging and human degenerative disease states [3235], this NFE2L2-KEAP1-PGAM5 ternary interaction may be an important mechanism in the development of human diseases.…”
Section: Mitochondria and Antioxidant Defensementioning
confidence: 99%
“…When we analyzed the top five proteins with significantly increased abundance, we identified PARL as a candidate for further study due to its role in regulating mitochondrial responses to stress, such as membrane depolarization and increased reactive oxygen species (2224). Additionally, dysregulation of PARL substrates has been implicated in cardiomyopathy and cardiac development, further highlighting the potential role of PARL dysregulation in BTHS (25–27). Upon further investigation of the 127 terms significantly enriched for proteins with a FC > 1.20, we observed that 20 terms reference the mitochondrion or mitochondrial dynamics, including: metabolic pathways (p=3.1 × 10 −3 ), positive regulation of the apoptotic process (p=4.2 × 10 −3 ), and mitochondrial inner membrane (p=5.2 × 10 −3 ) (Table S2B).…”
Section: Resultsmentioning
confidence: 99%
“…When we analyzed the top five proteins with significantly increased abundance, we identified PARL as a candidate for further study due to its role in regulating mitochondrial responses to stress, such as membrane depolarization and increased reactive oxygen species (22)(23)(24). Additionally, dysregulation of PARL substrates has been implicated in cardiomyopathy and cardiac development, further highlighting the potential role of PARL dysregulation in BTHS (25)(26)(27). Upon further investigation of the 127 terms significantly enriched for proteins with a FC > 1.…”
Section: Functional Annotation Analysis: Proteins Of Respiratory Compmentioning
confidence: 99%